Analisis Faktor-Faktor yang Menentukan Kinerja Karyawan di PT. Arta Boga Cemerlang Denpasar - Suartama, Made Mahardika; Ardana, Komang (E-Jurnal Manajemen; Vol 3 No 5 (2014), 2014)
An organization can not flourish if their employees are also not experience performance improvement, especially with the increasing levels of competition in the business world. According to Shariff (2010) the performance of employees, generally refers to behavior that is relevant to the goals of the organization and which are under the control of the individual employee. Sanderson (2009) conducted a study on the importance of employee performance, it was found that the organization needs to focus on strengthening the management to improve employee performance. This is important in order to increase employee loyalty and gain the trust of consumers so that consumers satisfied and loyal to the company. Zahargier (2011) mentions the employees in the company are required to commit to the performance standards by improving performance to achieve and maintain a competitive advantage for a long time. In order to produce optimum performance must not be separated from the role of management to pay attention to the factors that influence employee performance. PT. Arta Boga Shining Denpasar as the study draws attention to the factors that determine the performance of employees, namely: leadership, financial compensation, education and training, stress and work discipline. Based on the fact, found some employee complaints and problems that occur with regard to the factors that determine the performance of employees. The purpose of the study was to determine the factors that determine the performance of employees and to determine the dominant variables of each factor in determining the performance of employees at PT. Arta Boga Shining Denpasar. The research sample is determined by the method of stratified random sampling as many as 89 employees. Analysis using confirmatory factor analysis. Based on the analysis it was found that the factors that determine the performance of employees at PT . Arta Boga Shining Denpasar are: leadership, education and training, financial compensation, stress and work discipline. Dominant variables of each factor in determining the performance of employees is: a leader's ability to lead is the dominant variable of the factors of leadership, financial compensation in accordance with the demands of the job is the dominant variable of financial compensation factor, positive effect on the organization of education and training is variable the dominant factors of education and training, the demands of the task is the dominant variable stress factors, and carry out the instructions of the leader is the dominant variable factor in determining the performance of the work discipline of employees.
Keywords: organizational behavior, performance, loyalty.